WAR MEMORIES OF CHILDREN AS A SOURCE OF THE HISTORY OF DAGESTAN DURING THE YEARS OF THE GREAT PATRIOTIC WAR - Mirzabekov, M A; Kajmarazova, L G; Lysenko, U M (History, Archeology and Ethnography of the Caucasus, 2016)
Using the recollections of the war children the authors of the article attempt to fill in the gap in interpretation of history of Dagestan during the Great Patriotic War of 1941–1945 for multiaspect reconstruction of economic, political and cultural space. The authors consider recollections to be a mass source of personal provenance as they carry historical information which is not presented in other sources, and explain them to create historical research in terms of increasing attention to the man in history, to “living history”, history of everyday life.